The relationship between pre-landfall intensity change and post-landfall weakening of tropical cyclones over China - Han, Wenjun; Wang, Yuqing; Liu, Lu (Frontiers in Earth Science, 2022)
The accurate prediction of the weakening of landfalling tropical cyclones (TC) is of great importance to the disaster prevention but is still challenging. In this study, based on the 6-hourly TC best-track data and global reanalysis data, the relationship between the intensity change prior to landfall of TCs and the energy dissipation rate after landfall over mainland China is statistically analyzed, and the difference between East and South China is compared. Results show that TCs making landfall over East China often experienced pre-landfall weakening and usually corresponded to a rapid decay after landfall, while most TCs making landfall over South China intensified prior to landfall and weakened slowly after landfall. The key factors affecting both pre-landfall intensity change and post-landfall energy dissipation rate are quantitatively analyzed. It is found that the decreasing sea surface temperature (SST), increasing SST gradient, and increasing environmental vertical wind shear are the major factors favoring high pre-landfall weakening occurrence, leading to rapid TC weakening after landfall over East China. In South China, changes in the large-scale environmental factors are relatively small and contribute little to the post-landfall weakening rate.